Poly(azomethine-urethane) and zeolite-based composite: Fluorescent biosensor for DNA detection - Kamaci, Umran Duru; Kamaci, Musa; Peksel, Aysegul (PERGAMON-ELSEVIER SCIENCE LTD, 2019)
In the present paper, a highly selective and sensitive fluorescent biosensor based on poly(azomethine-urethane) and zeolite for the determination of DNA molecules was developed. Zeolite was chosen to enhance with anionic or cationic functional groups in polymer matrix and interaction between polymer and DNA. Several parameters such as polymer concentration, pH and incubation time effect on the sensitivity of the fluorescent biosensor were optimized. Linear range was determined between 2.50 and 25.00 nmol/L DNA concentration and limit of detection (LOD) of the biosensor was calculated as 0.095 nmol/L under the optimal conditions. Interference study was also performed in the presence of different amino adds, cations and organic compounds. The results dearly indicated that the tested cations and compounds were not induced a significant fluorescence change and the proposed zeolite-based biosensor was shown a good selectivity for DNA. (C) 2019 Elsevier B.V. All rights reserved.
Keywords: Zeolite; DNA; Fluorescent sensor; Biosensor; GRAPHENE OXIDE; QUANTUM DOTS; SCHIFF-BASE; PLATFORM; GOLD; NANOCOMPOSITE; CONSTRUCTION; ELECTRODE; GUANINE; SENSORS; Spectroscopy